2021
DOI: 10.1021/acs.jcim.1c00679
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based de Novo Molecular Generator Combined with Artificial Intelligence and Docking Simulations

Abstract: Recently, molecular generation models based on deep learning have attracted significant attention in drug discovery. However, most existing molecular generation models have a serious limitation in the context of drug design wherein they do not sufficiently consider the effect of the three-dimensional (3D) structure of the target protein in the generation process. In this study, we developed a new deep learning-based molecular generator, SBMolGen, that integrates a recurrent neural network, a Monte Carlo tree s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 50 publications
0
54
0
Order By: Relevance
“…3 Recently, deep learning has been applied towards more efficient methods of sampling chemical space such that it is possible to identify promising candidate molecules faster. Deep generative models using policy based reinforcement learning (RL) [4][5][6][7][8][9][10] , value based RL 11 , learning a molecular latent space 12 , and other methods including tree search 13 and genetic algorithms [14][15][16] have been proposed to generate molecules that possess a desired set of properties. In the policy based RL paradigm, an agent (a generative model) learns a policy (series of actions to take at given states) to generate molecules that maximize a reward which is typically computed based on a predefined reward function.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recently, deep learning has been applied towards more efficient methods of sampling chemical space such that it is possible to identify promising candidate molecules faster. Deep generative models using policy based reinforcement learning (RL) [4][5][6][7][8][9][10] , value based RL 11 , learning a molecular latent space 12 , and other methods including tree search 13 and genetic algorithms [14][15][16] have been proposed to generate molecules that possess a desired set of properties. In the policy based RL paradigm, an agent (a generative model) learns a policy (series of actions to take at given states) to generate molecules that maximize a reward which is typically computed based on a predefined reward function.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we demonstrate that simple curricula, utilizing a single Curriculum Objective can accelerate agent productivity and generate compounds that satisfy a docking constraint, i.e., predicted to retain experimentally validated interactions (see Methods for experiment hyperparameters). 6,7,[13][14][15] Simulating a real-world application where one must allocate limited computational resources, baseline RL and CL performances are compared, given a maximum number of permitted production epochs (300), i.e., epochs that involve docking, as these are relatively computationally demanding. For CL, Curriculum Objectives are first applied to guide the agent and the number of permitted curriculum epochs is not limited, as these are computationally inexpensive (see Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…3 Recently, deep learning has been applied towards more efficient methods of sampling chemical space such that it is possible to identify promising candidate molecules faster. Deep generative models using policy-based reinforcement learning (RL) [4][5][6][7][8][9][10] , value based RL 11 , learning a molecular latent space 12 , and other methods including tree search 13 and genetic algorithms [14][15][16] have been proposed to generate molecules that possess a desired set of properties. In the policy-based RL paradigm, an agent (a generative model) learns a policy (series of actions to take at given states) to generate molecules that maximize a reward which is typically computed based on a pre-defined reward function.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the method finds compounds with high affinity for a given target protein more efficiently than reinforcement-based algorithms. Ma et al suggested a structure-based de novo molecular generator approach, SBMolGen, by combining an RNN-based SMILES generator and a Monte Carlo tree search with docking simulations [ 25 ]. In the SBMolGen approach, a generated molecule is docked with a target protein, and the result is used to provide feedback to the generator to optimize the docking score.…”
Section: Introductionmentioning
confidence: 99%